Regulatory arbitrage and the expansion of shadow banks in the U.S. mortgage market - Gaião, Camila da Paz Campos (2021)
Shadow banks' market share in the mortgage market of the US has increased from 23,5% in 2009 to 57,6% in 2019. The residential mortgage market has changed dramatically in the years following the Great Recession: credit intermediation has shifted from traditional banks to shadow banks. For instance, Quicken Loans – the leading shadow bank – has become the largest mortgage lender in the United States in 2019, overtaking for the first time Wells Fargo – the historical market leader. The present research uses panel data models to show an essential aspect behind the transformation of the mortgage market herein described: the impact of the regulatory burden on 'traditional' bank lending in the USA. The research design contemplates two main regulatory variables, as well as several banking and macroeconomic control variables. To this end, annual data were extracted from the Consumer Financial Protection Bureau (CFPB), the Home Mortgage Disclosure Act (HMDA), and FRED databases. In the aftermath of the Great Recession, supervision increased, and 'traditional' banks were forced to cut back on riskier lending. Shadow banks - which fall outside the scope of conventional regulation – duly filled this market gap. The present Dissertation sustains this argument by demonstrating that stricter regulatory requirements constrain the mortgage lending growth of traditional banks, thus benefiting US shadow banks' intermediation activities, as confirmed by the two main regulatory variables herein used. Our baseline findings are subject to stringent robust testing across specifications, suggesting the findings are globally stable.